2003
DOI: 10.1128/jcm.41.12.5604-5608.2003
|View full text |Cite
|
Sign up to set email alerts
|

Concordance ofHelicobacter pyloriStrains within Families

Abstract: Helicobacter pylori infection is typically acquired in early childhood, and a predominantly intrafamilial transmission has been postulated. To what extent family members share the same strains is poorly documented. Our aim was to explore patterns of shared strains within families by using molecular typing. Family members of H. pylori-infected 10-to 12-year-old index children identified in a school survey were invited to undergo gastroscopy. Bacterial isolates were typed with random amplified polymorphic DNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
100
1
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 40 publications
6
100
1
7
Order By: Relevance
“…The importance of both infected siblings and mothers was recently corroborated in a Brazilian high-prevalence community [41]. The findings are substantiated by a previous report of H. pylori strain concordance between mothers and offspring and amongst siblings, demonstrated by using bacterial molecular typing in a subset of the currently studied families [40]. Aguemon et al also reported the higher infection rate in children whose parents were both infected or only infected mother.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The importance of both infected siblings and mothers was recently corroborated in a Brazilian high-prevalence community [41]. The findings are substantiated by a previous report of H. pylori strain concordance between mothers and offspring and amongst siblings, demonstrated by using bacterial molecular typing in a subset of the currently studied families [40]. Aguemon et al also reported the higher infection rate in children whose parents were both infected or only infected mother.…”
Section: Discussionsupporting
confidence: 70%
“…Malaty et al also provided data demonstrating an increased prevalence of infected children to infected parents [4,39]. The higher prevalence of infection due to H. pylori in parents of infected children suggests person-to-person transmission within the family [5,40]. The H. pylori status of the mother was found to be a strong determinant for childhood infection and more predictive than the status of the father [13,14,36].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…pylori are highly genetically diverse, providing Ϸ1,400 informative sites within 4.5 kb of sequence, and their global genetic structure parallels that of humans (28). Moreover, epidemiological studies have shown that transmission occurs predominantly within families (29)(30)(31)(32). This point is critical because vertical transmission is more likely to reflect human migrations than is the horizontal transmission that is typical of many microbes.…”
mentioning
confidence: 99%
“…Epidemiological and molecular fingerprinting data suggest that the transmission of Helicobacter pylori occurs from person to person during childhood, without an animal or environmental reservoir (2,9,10,(16)(17)(18). The relative importance of fecaloral transmission versus that of oral-oral transmission is controversial (7,13,14).…”
mentioning
confidence: 99%